Study the influence of the depth of the metal Skirt under strip foundation resting on sand on bearing capacity and settlement - ناصر بشرى; صفوان عبدالله (Tishreen University Journal -Engineering Sciences Series,, 2023)
The sandy weak endurance soils, which have large settlements, are considerate of the most geotechnical common problems. In order to improve the bearing capacity of the soil and reduce the settlement of the foundation based on this type of soil, has been proposed a number of ways to improve the soil such as: replace the thickness of certain soil by other good endurance soil, add items to improve the soil, supported the soil by different types of the structural elements as Geotextile or use a metal skirt on both ends of the foundation, etc. This study has been realized in two phases: the first phase consists in establishing a numerical model for skirt with two branches under a strip foundation resting on sand by using finite element analyses program (PLAXIS2D) and determining the footing settlement and compared the results with the experimental ones (reference case).A close agreement between experimental and numerical curves is noticed.The second phase deals with studying the effect of changing the depth of the skirt on the bearing capacity of the soil and its settlement and this study show the depth of the skirt has an influence on the bearing capacity of the soil and its settlement , it was adoption the depth of the skirt (1.5B), for economically and safety for being reduces the value of settlements under strip foundation by (38.15%), and raises the bearing capacity the soil by (36.5%) in a way of forces.